Sex difference in the associations among liver function parameters with incident diabetes mellitus in a large Taiwanese population follow-up study - Chen, Yi-Kong; Wu, Pei-Yu; Huang, Jiun-Chi; Chen, Szu-Chia; Chang, Jer-Ming (Frontiers in Public Health, 2023)
Background The prevalence of diabetes mellitus (DM) in Taiwan between 2017 and 2020 was 11.05%, which is higher than the global prevalence (10.5%). Previous studies have shown that patients with DM have higher liver enzyme levels than those without DM. However, it is unclear whether there are sex differences in the association between incident DM and liver function. Therefore, the aim of this longitudinal study was to investigate this issue in a large Taiwanese cohort. Methods We identified 27,026 participants from the Taiwan Biobank, and excluded those with baseline DM (n = 2,637), and those without follow-up data on DM, serum fasting glucose or glycosylated hemoglobin A1c (n = 43). The remaining 24,346 participants (male: 8,334; female: 16,012; mean age 50.5 ± 10.4 years) were enrolled and followed for a median of 4 years. Results Of the enrolled participants, 1,109 (4.6%) had incident DM and 23,237 (95.4%) did not. Multivariable analysis showed that high levels of glutamic-oxaloacetic transaminase (AST) (p < 0.001), glutamic-pyruvic transaminase (ALT) (p < 0.001), albumin (p = 0.003), α-fetoprotein (p = 0.019), and gamma-glutamyl transpeptidase (GGT) (p = 0.001) were significantly associated with incident DM in the male participants. In comparison, high levels of AST (p = 0.010), ALT (p < 0.001), albumin (p = 0.001) and GGT (p < 0.001), and low total bilirubin (p = 0.001) were significantly associated with incident DM in the female participants. There were significant interactions between total bilirubin and sex (p = 0.031), and GGT and sex (p = 0.011) on incident DM. Conclusion In conclusion, liver function parameters were significantly associated with incident DM. Further, there were differences in the associations between the male and female participants.